Blue Ocean Strategy and Beyond Disruption Collection (2 Books). - Kim, W. Chan; Mauborgne, Renée; Kim, W. Chan.; Kim, W. Chan. (Boston, Massachusetts : Harvard Business Review Press, 2024)
The two landmark books, Blue Ocean Strategy and Beyond Disruption, that together challenge everything you thought you knew about winning the future. These two iconic books, Blue Ocean Strategy and Beyond Disruption, together changed how the world thinks about strategy and innovation. Blue Ocean Strategy, the #1 global bestseller, reframed strategy not as a game between rivals fighting over markets and customers but as a new approach to creating markets and attracting customers--in untapped new market spaces free of competition. Just as Blue Ocean Strategy redefines the essence of strategy, Beyond Disruption redefines and expands the existing view of innovation by introducing a new approach, nondisruptive creation, that is free from the destructive displacement of jobs, people, companies, and industries that happens when companies set out to disrupt. Taken together, these bestselling books will help you chart a bold new path to winning the future.
Blue ocean strategy (expanded edition) / W. Chan Kim and Renée Mauborgne -- Beyond disruption / W. Chan Kim and Renée Mauborgne.
Description based upon print version of record.
Added to collection customer.56279.3
Keywords: Market segmentation; Economics; Competition; Technological innovations; Success in business; Economic development; Business ethics; Disruptive technologies; Segmentation du marché; Économie politique; Innovations; Succès dans les affaires; Développement économique; Morale des affaires; Technologie de rupture; economics; economic development